Molecular genetic techniques in current biomedical research. Part I: Theoretical basis of PCR -diagnostics - A. N. Volkov; L. V Nacheva (Фундаментальная и клиническая медицина, 2020)
Molecular genetic techniques represent an essential part of current biomedical research. Among them, polymerase chain reaction (PCR) is the most widespread. This approach reproduces the natural mechanism of nucleic acid replication in vitro, specifically restricted to the region of interest. PCR permits fast and highly specific amplification of the genome fragments belonging to any organism. Therefore, the applications of PCR diagnostics vary from identifying infectious agents to establishing causes of hereditary and multifactorial diseases and to personal identification in forensic medicine. The proposed lecture course discusses the PCR principles and cases of its application in biomedical research. Here we describe theoretical concepts and molecular basis of PCR diagnostics as well as chemical features of the nucleic acids. Particular attention is paid to the technical solutions extending the applicability of PCR and to the manipulations for its successful use. The lecture is primarily aimed at biomedical students and junior researchers.